Regulation of BC200 RNA‐mediated translation inhibition by hnRNP E1 and E2. Issue 2 (12th January 2017) - Jang, Seonghui; Shin, Heegwon; Lee, Jungmin; Kim, Youngmi; Bak, Geunu; Lee, Younghoon
Abstract : The long noncoding RNA BC200 (brain cytoplasmic RNA, 200 nucleotides) acts as a translational modulator of local protein synthesis at dendrites. BC200 RNA has been shown to inhibit translation in vitro, but it remains unknown how this translation inhibition might be controlled in a cell. Here, we performed yeast three‐hybrid screening and identified hnRNP E1 and hnRNP E2 as BC200 RNA‐interacting proteins. We found that: these hnRNA proteins could restore BC200 RNA‐inhibited translation; BC200 RNA interacts with hnRNP E1 and E2 mainly through its unique 3′ C‐rich domain; and the RNA binding specificities and modes of the two proteins differed somewhat. Our results offer new insights into the regulation of BC200 RNA‐mediated translation inhibition. Abstract :